An Electromagnetic Field Concentrator for Process Chambers - Piotr Paplicki; Piotr Strobejko (Energies)
This paper describes selected results of the design and optimization of an electromagnetic field concentrator (MFC) for process chambers. On the basis of 2D/3D FE analysis, it was confirmed that the presented new structure for an electromagnetic field concentrator with three-phase windings and an additional DC central coil excites, in the working space of the device, a steady or time-varying magnetic field with adjustable peak value, pulsation amplitude and vector magnetic field orientation. The presented field concentrator can be used for process chambers carrying out chemical, biological, thermal and measurement processes, among others.